2016
DOI: 10.4103/1305-7456.175693
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of superoxide dismutase, alpha-tocopherol, and 10% sodium ascorbate on reversal of shear bond strength of bleached enamel: An in vitro study

Abstract: Objective:The aim of this study was to investigate the neutralizer effect of antioxidant agents on the bond strength of bleached enamel.Materials and Methods:Sixty enamel slabs were prepared from 60 freshly extracted maxillary central incisors and were divided into six groups. The negative control group received no bleaching treatment and the other groups were bleached with 35% carbamide peroxide (Opalescence Quick; Ultradent, South Jordan, USA). In Group II, composite was built immediately after bleaching and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 27 publications
2
44
2
3
Order By: Relevance
“…Aiming to reduce this time interval, the antioxidant products were introduced as an interesting strategy since they can remove or reduce the residual oxygen (8,9). Sodium ascorbate is one of the most studied antioxidants, however, despite its efficiency (7,8,(10)(11)(12), there is still controversy regarding its action mechanisms (9). In addition, Ozelin et.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to reduce this time interval, the antioxidant products were introduced as an interesting strategy since they can remove or reduce the residual oxygen (8,9). Sodium ascorbate is one of the most studied antioxidants, however, despite its efficiency (7,8,(10)(11)(12), there is still controversy regarding its action mechanisms (9). In addition, Ozelin et.…”
Section: Introductionmentioning
confidence: 99%
“…This waiting period may vary, according to the bleaching gel concentration and time established for the bleaching procedure. 7,8,19 This phenomenon may have influenced the reduction in bond strength values in G4 (9.22 MPa) relative to the control group (14.61 MPa). This 36.8% difference was statistically significant and demonstrates that 24 hours of post-bleaching storage in AS is not enough for the oxygen release, especially after 28 days of bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested there is an adhesive reduction when restorative procedures are performed following a bleaching procedure. 6,8 There is a lack of studies focussed on the influence of extended bleaching on the bond strength of restorative materials to enamel. Therefore, the aim of this in vitro study was to determine the influence of 4% hydrogen peroxide with calcium on enamel bond strength under different gel exposing times, as well as dissimilar storage periods after bleaching.…”
Section: Introductionmentioning
confidence: 99%
“…Alguns autores afirmam que este procedimento altera a superfície do esmalte enquanto outros defendem a ideia de que o oxigênio residual da reação de clareamento interfere na adesão ao substrato (COTTON;WILKINSON, 1972;SMITH, 1988;HEYMANN, 1991;DISHMAN;COVEY;BAUGHAN, 1994;GREGUS;KLAASSEN, 1995;MURAGUCHI et al, 2007;MINOUX;SERFATY, 2008;SULIEMAN, 2008;BITTENCOURT et al, 2010;BRISO et al, 2012). Levando em consideração a segunda hipótese, algumas estratégias vêm sendo estudadas com o intuito de remover o oxigênio residual precocemente e melhorar a adesão em dentes clareados, dentre as quais destacam-se as substâncias antioxidantes (LAI et al, 2001;TURKUN, 2003;KOGA;BORGES, 2006;MURAGUCHI et al, 2007;SASAKI;FLÓRIO;BASTING, 2009;GARRIDO, 2011;GARCIA et al, 2012;TOSTES et al, 2013;BERGER et al, 2013;ALENCAR et al, 2016;KAVITHA et. al, 2016).…”
Section: Grau De Conversão Avaliado Por Espectroscopia Micro-ramanunclassified
“…Diante disto, no presente trabalho, optou-se por avaliar o bicarbonato de sódio por ser uma substância de fácil obtenção, uma vez que acompanha a maioria dos kits de clareamento (TOSTES et al, 2013;ALENCAR et al, 2016). De acordo com a literatura, dentre os testes que avaliam o comportamento das restaurações adesivas em esmalte clareado, destacam-se o teste de cisalhamento (KIMYAI;VALIZADEH 2006;KOGA;BORGES, 2006;MURAGUCHI et al 2007;GÖKÇE et al 2008;TÜRKÜN;ARICI, 2008;SASAKI;FLÓRIO;BASTING, 2009;AGHELINEJAD, 2011;MAZAHERI et al, 2011;SHARAFEDDIN;FARSHAD, 2015;KAVITHA et al, 2016) e microtração (LAI et al, 2002ARCARI et al, 2007;CHUANG et al, 2009;BARCELLOS et al, 2010;LAGO, DE FREITAS;NETTO, 2011;ROCHA GOMES TORRES et al, 2012;OZELIN et al, 2014;ALENCAR et al, 2016 , 2014;LOGUERCIO et al, 2015;CARDENAS et al, 2016). Isso se deve ao fato de que os monômeros acídicos presentes na sua composição não serem capazes de produzir um padrão de condicionamento tão retentivo como o obtido através do uso do ácido fosfórico (HANNING et al, 2002;PERDIGÃO E GERALDELI, 2003;VAN LANDUYT et al, 2007, CARDENAS et al, 2016.…”
Section: Grau De Conversão Avaliado Por Espectroscopia Micro-ramanunclassified